Effects of comorbidity and hospital care on 6-month mortality in patients with elevated cardiac troponin T. Issue 979 (8th May 2007) - Wong, P; Ramsewak, A; Murray, S; Robinson, A; Robinson, D; Rodrigues, E
Abstract : Objective: To examine the effects of comorbidity and hospital care on mortality in patients with elevated cardiac troponin T. Design: Observational study. Setting: A large university hospital with on-site diagnostic cardiac catheter laboratory. Patients: All hospitalised patients with elevated cardiac troponin T level (⩾0.01 μg/l) over an 8-week period. Main outcome measures: 6-month all-cause mortality. Results: Among 313 patients with elevated cardiac troponin T, 195 had acute coronary syndrome and 118 had other conditions. Multivariate analysis showed that among patients with acute coronary syndrome, increasing comorbidity score (odds ratio (OR) 1.23 per point increase, 95% confidence interval (CI) 1.00 to 1.51; p = 0.048), age (OR 1.08 per year, 95% CI 1.04 to 1.13; p<0.001), raised troponin T level (OR 2.22 per 10-fold increase, 95% CI 1.27 to 3.89; p = 0.005), and ST depression (OR 3.12, 95% CI 1.38 to 7.03; p = 0.006) were independent adverse predictors, while cardiologist care (OR 0.22, 95% CI 0.09 to 0.51; p<0.001) was associated with a better survival. Increasing troponin T level (OR 3.33 per 10-fold increase, 95% CI 1.24 to 8.91; p = 0.017) was found to predict a worse prognosis among patients without acute coronary syndrome, and cardiologist care did not affect outcome in this group. Among hospital survivors with acute coronary syndrome, increasing comorbidity score, age and a lack of cardiologist care were independently associated with lesser use of effective medications. Conclusions: Comorbidity was associated with a higher 6-month mortality in patients having acute coronary syndrome, and lesser use of effective medicines among hospital survivors. Cardiologist care was associated with better 6-month survival in patients with acute coronary syndrome, but not in those without acute coronary syndrome.